2008
DOI: 10.1179/136404608x361800
|View full text |Cite
|
Sign up to set email alerts
|

In situobservation of nucleation, fragmentation and microstructure evolution in Sn–Bi and Al–Cu alloys

Abstract: This paper presents recent progress of in situ observation for the microstructure evolution during solidification. Nucleation and fragmentation of dendrite arms are important issues for controlling microstructure during solidification. However, there are few studies on in situ observation of nucleation and fragmentation in metallic alloys. Time resolved X-ray imaging technique has been developed to observe solidification of metallic alloy systems in situ. Fragmentation of dendrite arms often occurred at the ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
18
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(19 citation statements)
references
References 11 publications
(4 reference statements)
1
18
0
Order By: Relevance
“…[9][10][11][12][13][14][15][16][17] The in situ observations of deformation at the grain scale in semi-solid Al-Cu alloys and carbon steels have been carried out using similar techniques. [18][19][20][21][22] Past research [18][19][20][21][22] showed that shear-induced dilation occurred by grain rearrangement including rotation and translation of solid particles in response to a force chain network at the low shear rate of 10 À3 to 10 À2 /s.…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11][12][13][14][15][16][17] The in situ observations of deformation at the grain scale in semi-solid Al-Cu alloys and carbon steels have been carried out using similar techniques. [18][19][20][21][22] Past research [18][19][20][21][22] showed that shear-induced dilation occurred by grain rearrangement including rotation and translation of solid particles in response to a force chain network at the low shear rate of 10 À3 to 10 À2 /s.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] In the third generation synchrotron radiation facilities such as SPring-8, 21) hard X-rays with photon energy ranging from 10 to 100 keV can be used for the Xray imaging. The hard X-ray penetrates through bulk specimen of metallic materials.…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14][15][16][17][18][19][20][21] Recently a similar technique has been applied to in-situ observation of shear deformation in semi-solid Al-Cu and Fe-C alloys. [22][23][24] The time-resolved sequence of images showed impingement between solid particles and the translation and rotation of solid particles about their contacts in response to shear at the grain scale.…”
Section: Introductionmentioning
confidence: 99%